Optimization of fixture locating layout for sheet metal part by cuckoo search algorithm combined with finite element analysis - Yang, Bo; Wang, Zhongqi; Yang, Yuan; Kang, Yonggang; Li, Cheng (Advances in mechanical engineering, 2017)
Fixture layout has a direct and influential impact on sheet metal manufacturing quality. Much attention has been paid to sheet metal fixture locating layout in the fields of academy, engineering, and industry in the past few years. However, how to obtain the optimal fixture locating layout so as to effectively reduce the sheet metal part deformation is still a complex and challenging task. To that end, this article proposes a new approach to optimizing the sheet metal fixture locating layout based on the “N-2-1” locating principle by coupling cuckoo search algorithm with finite element analysis. First, the optimization model of the sheet metal locating layout based on the “N-2-1” locating principle is constructed. Second, the cuckoo search algorithm is employed to search the optimum layout of the “N” fixture locators for the minimum deformation through iterative calls to the finite element analysis solver. Finally, two cases are respectively studied and conducted to verify the proposed method, and the comparison results with genetic algorithms and particle swarm optimization show that the cuckoo search algorithm outperforms the genetic algorithms and particle swarm optimization in terms of the quality of the solutions, robustness, and usability in the sheet metal fixture locating layout optimization.